An Analysis of Illocutionary Act in Incredible 2 Movie - Partohap Saut Raja Sihombing; Dumaris E. Silalahi; Debby Intragedy Saragih; Herman Herman (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The objective of this research is to analyze the types of illocutionary act in the Incredible 2 movie and to interpret the dominant types of illocutionary act. Searle’s theory are used by the researchers to answer the formulated research questions. This research is a qualitative research applying content or document analysis. The subject of this research is a movie entitled Incredible 2  movie The data were some scene including the illocutionary act in Incredible 2 movie. To collecting the data, the researchers downloading the movie from google, watching the film “Incredible 2” for several time, then searching for the script of the movie in the internet, watching the movie while reading the script, finding some sentences that are considered to have illocutionary act needed for the analysis and found the dominant types of illocutionary act, After collected the data, the researchers analyze the data based on some steps, classifying the illocutionary act, finding the dominant types of the illocutionary act, The findings of the research are as follows: in Incredible Movie, Searle’s theory there are 5 types of illocutionary act are found: From those types, in movie Incredible  found the types of illocutionary act as follows : directives consist of  8 data (32%), assertive consist of 7 data (28%), expressive consist of 7 data (28%), commisive consist of 2 data (8%) and declaration sonsist of 1 data(4%).